The State teaches about native languages: a reflection from the programme "Aprendo en Casa": una reflexión desde el programa “Aprendo en Casa” (Revista Peruana de Investigación Educativa, 2020)
In this article, we make a critical analysis of the programme on "Indigenous and native languages of Peru" transmitted on "Aprendo en Casa" by the Peruvian national television during the COVID-19 pandemic. We focus on three aspects of how the program deploys a dominant discourse around native languages and their speakers, with the aim of unraveling its rationalities and strategies. In the first section, we report on the rhetoric of a 'discourse of endangerment' that has become established as the 'natural' way of speaking about minoritized languages. In the second section, we show that this discourse projects a celebratory multilingualism and denies antagonisms. In the third and final one, we analyse the essentialising relationship between language, culture, identity and territory, which ends up excluding people who identify with the indigenous languages but do not fit into this equation. We argue that the discourse analyzed is linked to the management of diversity within the framework of the new globalized economy and with a neoliberal multiculturalism that has prevailed in Peru for several decades. Likewise, we maintain that this way of dealing with native languages is far from a language education necessary for the critical formation of learners.
Keywords: multilingualism, language policy, intercultural bilingual education, Quechua, critical discourse analysis